The posttranslational modifications of Hippo-YAP pathway in cancer - Yan, Fangjie; Qian, Meijia; He, Qiaojun; Zhu, Hong; Yang, Bo (Biochimica et biophysica acta. General subjects, 2020)
Yes-associated protein (YAP) is a key effector of the Hippo pathway and is frequently dysregulated in aggressive human cancers. Aberrant YAP activation has emerged as an important driver of tumorigenesis, chemoresistance and metastasis. Since posttranslational modifications (PTMs) are pivotal modifiers that determine protein activation or subcellular localization, the malfunction of YAP due to dysregulated PTMs has been linked to various cancers. Collectively, although YAP has long been considered an “undruggable” transcription cofactor, its PTMs may be its “Achilles' heel”. To provide theoretical support for developing small molecule inhibitors based on PTMs, in this review article, we summarize the current understanding of the impact of PTMs in regulating the Hippo-YAP pathway and further discuss potential therapeutic intervention. In our review, we summarize the known posttranslational modifications (PTMs) of YAP that dictate its protein stability, transcriptional activity and subcellular localization at different stages. Here, we clearly summarize the specific enzymes and sites involved in YAP PTMs and place additional focus on the consequences of PTM-modulated YAP activity and translocation. PTMs of YAP play fundamental roles in controlling the protein abundance and function. Therefore, interfering with PTMs of YAP may contribute to solving the “undruggable” problem in YAP inhibition, thus providing new approaches for YAP-based cancer therapy. Future studies that target corresponding PTM-related kinases/enzymes will provide new strategies for cancer therapy, particularly in tumors with YAP dysregulation. •YAP is a transcriptional cofactor and generally dysregulated in cancers.•Posttranslational modifications dictate diverse aspects of YAP activity.•Targeting PTMs may be an effective strategy to inhibit YAP-mediated tumorigenesis.